2000
DOI: 10.1038/sj.onc.1203742
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the human endogenous retrovirus-like element HERV-E.PTN on the expression of growth factor pleiotrophin: a critical role of a retroviral Sp1-binding site

Abstract: Germ line insertion of a human endogenous retroviruslike element (HERV-E.PTN) into the growth factor pleiotrophin (PTN) gene generated a phylogenetically new promoter driving the expression of functional HERV-PTN fusion transcripts. Here we show by in situ hybridization, that HERV-PTN fusion transcripts are expressed in malignant trophoblasts (i.e. choriocarcinoma) and in the proliferative and in the invasive trophoblasts of gestational trophoblastic tissue. Additionally, a 1.9 kb fragment of the HERV-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 45 publications
0
33
0
1
Order By: Relevance
“…A putative binding site for the placental transcription factor Hand1͞E47 was identified in the EDNRB LTR promoter and was shown to be important for placenta-specific promoter activity, but interaction of Hand1͞ E47 with this site could not be confirmed (11). In other studies, only ubiquitous transcription factors have been confirmed to bind LTR gene promoters (10,12). Therefore, the transcription factors that mediate tissue-specific gene expression from LTR promoters remain largely unknown.…”
mentioning
confidence: 99%
“…A putative binding site for the placental transcription factor Hand1͞E47 was identified in the EDNRB LTR promoter and was shown to be important for placenta-specific promoter activity, but interaction of Hand1͞ E47 with this site could not be confirmed (11). In other studies, only ubiquitous transcription factors have been confirmed to bind LTR gene promoters (10,12). Therefore, the transcription factors that mediate tissue-specific gene expression from LTR promoters remain largely unknown.…”
mentioning
confidence: 99%
“…Ancient retroviral inserts express Sp1-binding sites (species-specifi c gene expression stimulatory proteins binding to GC box GGGCGGG motifs). In the drosophila genome, proto-oncogene expressions are intensifi ed by Sp1-stimulated retroviral inserts [90][91][92]. In general, ancient retroviral inserts are activators of protooncogenes [1,93].…”
Section: Drosophilamentioning
confidence: 99%
“…Deletion of the retroviral-derived section of the promoter sequence prevented the growth, invasion and angiogenesis that would normally accompany the tumour development. 43 In an elegant body of work over the last decade, Roemer, Armbruester and colleagues have presented a growing litany of evidence for the fact that HERV-K viruses may play significant roles in carcinogenesis. They first noticed the association between high titres of antibodies to HERV gag and env and germ cell tumours, such as seminomas and teratocarcinomas.…”
Section: Hervs In Carcinogenesismentioning
confidence: 99%